(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The purpose of conducting this study is to find out the comparative effect of calisthenicsexercises on the cardio-respiratory endurance among various racket sports players. The study wasconducted by randomly selecting 30 male racket game players from sports specialization of badminton,table tennis and tennis with their age ranging between of 18 to 22 yearsfrom Lakshmibai NationalInstitute of Physical Education, North East Regional Centre, Guwahati, Assam. The total subjects (N=30)were further divided into two groups with 15 subjects experimental control group each. Theexperimental group was given 6-week calisthenic training program thrice a week for 45 minutes asession whereas the control group was not given any calisthenic training.Pre-test and post test wasconducted for all 30 subjects selected prior to and after the implementation of the calisthenics training,The data wasanalysed using mean and SD as descriptive statistics. To reveal the result on comparativeeffect of the training two-way ANOVA was employed and tested at 0.05 level of significance. The resultsrevealed that in the variable of cardio- respiratory endurance there was no significant differences seen inthe test scores, whereas, significant differences were seen between the experimental and control group